La mare de Déu de la Mercè a les illes gregues de Siros i Tinos - Janeras i Vilaró, Sebastià (Miscel·lània litúrgica catalana, 2022)
This paper discusses the existence and origin of chapels dedicated to Our Lady of Mercy, under this advocation or equivalent ones, on the Greek islands of Syros and Tinos in the Cyclades archipelago. These chapels areconnected with the establishment and presence of Catholic communities of the Latin rite on these islands.